2021
DOI: 10.1026/0049-8637/a000234
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Sense of University Belonging for the Psychological and Academic Adaptation of International Students in Germany

Abstract: Abstract. Although a sense of university belonging has been established as a crucial factor for students’ academic success and subjective well-being, little is known about its importance regarding the adaptation of international students in Germany. Likewise, few studies have addressed the long-term reciprocal relations of a sense of university belonging and psychological and academic outcomes. To close this research gap, we analyzed data from N = 3,837 international students with a set of cross-lagged panel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Previous studies have extensively explored the academic adaptation of international students worldwide, encompassing various regions such as Asian countries (Arief & Melati, 2017;Jang, 2018;Wachyunni et al, 2023), China (Hussain & Shen, 2019;San & Guo, 2022;Sheng et al, 2022;Wenyan et al, 2023), African countries (Owusu-Agyeman & Mugume, 2023), European countries (Campos et al, 2022;Yildirim et al, 2021), Russia (Beregovaya & Kudashov, 2019), and the United States (Park, 2016;Tutar, 2023). The overarching goal of these global studies was to discern patterns and identify gaps in understanding the academic adaptation of international students across diverse countries.…”
Section: Academic Adaptationmentioning
confidence: 99%
“…Previous studies have extensively explored the academic adaptation of international students worldwide, encompassing various regions such as Asian countries (Arief & Melati, 2017;Jang, 2018;Wachyunni et al, 2023), China (Hussain & Shen, 2019;San & Guo, 2022;Sheng et al, 2022;Wenyan et al, 2023), African countries (Owusu-Agyeman & Mugume, 2023), European countries (Campos et al, 2022;Yildirim et al, 2021), Russia (Beregovaya & Kudashov, 2019), and the United States (Park, 2016;Tutar, 2023). The overarching goal of these global studies was to discern patterns and identify gaps in understanding the academic adaptation of international students across diverse countries.…”
Section: Academic Adaptationmentioning
confidence: 99%
“…The feeling of being integrated in the group of fellow students is a major predictor of academic success and drop-out (cf. Yildirim et al, 2021). Certain results of the SeSaBa project (cf.…”
Section: Recommendations For Actionmentioning
confidence: 99%
“… 35 , 36 School belonging can positively affect various adaptive activities in college, both academically and interpersonally, and it has been found that the implementation of interventions that promote an individual’s school belonging can help him or her to establish positive relationships with others and enhance the individual’s adaptation. 37 To sum up, it can be inferred that school belonging plays a mediating role in self-esteem and sociocultural adaptation.…”
Section: Introductionmentioning
confidence: 99%